Pleiotropic genes affecting carcass traits in bos indicus (Nellore) cattle are modulators of growth - Pereira, Anirene G. T.; Utsunomiya, Yuri T. [UNESP]; Milanesi, Marco [UNESP]; Torrecilha, Rafaela B. P. [UNESP]; Carmo, Adriana S. [UNESP]; Neves, Haroldo H. R.; Carvalheiro, Roberto [UNESP]; Ajmone-Marsan, Paolo; Sonstegard, Tad S.; Sölkner, Johann; Contreras-Castillo, Carmen J.; Garcia, José F. [UNESP] (Public Library of Science (PLoS), 2016)
Two complementary methods, namely Multi-Trait Meta-Analysis and Versatile Gene-Based Test for Genome-wide Association Studies (VEGAS), were used to identify putative pleiotropic genes affecting carcass traits in Bos indicus (Nellore) cattle. The genotypic data comprised over 777,000 single-nucleotide polymorphism markers scored in 995 bulls, and the phenotypic data included deregressed breeding values (dEBV) for weight measurements at birth, weaning and yearling, as well visual scores taken at weaning and yearling for carcass finishing precocity, conformation and muscling. Both analyses pointed to the pleomorphic adenoma gene 1 (PLAG1) as a major pleiotropic gene. VEGAS analysis revealed 224 additional candidates. From these, 57 participated, together with PLAG1, in a network involved in the modulation of the function and expression of IGF1 (insulin like growth factor 1), IGF2 (insulin like growth factor 2), GH1 (growth hormone 1), IGF1R (insulin like growth factor 1 receptor) and GHR (growth hormone receptor), suggesting that those pleiotropic genes operate as satellite regulators of the growth pathway.